Novel recommendation system based on long‐term composition for adaptive web services. (17th March 2020) - Kirubanantham, P; Vijayakumar, G
ABSTRACT: In the era of digital web services, composition of features on the fly is inevitable. The Long‐term Composed Service (LCS) entertains the composition of features to any extent, since it has an open‐ended lifetime. In the proposed research work, we have intended to provide service support to run the business toward a long time commitment. Structure‐based recommended system for LCSs (RS‐LCSs) is proposed, where user queries and recent updation/requirements are considered for exhibiting the response through the system. In the proposed system, business has been regulated according to the time constraints. We have tested our proposed system on the standard benchmark dataset and quantitative metrics show our proposed method has performed well against the compared methods. The forecasting of business has been done through our model to address the recent queries and new requirements issues to provide an adaptive web service for the business development.